A Sociological Analysis of Employment Discrimination Against Women in Pakistan - Shabana Muhammad Anwar; Qurratul Ain Sardar; Anam Aqil Khan (Journal of Management Practices, Humanities and Social Sciences, 2022)
In Pakistan, women treat not equally as a man in every stage of life. The patriarchal system of Pakistan retains women behindhand the man and generates inequalities to have equal social and economic opportunities of life enjoyment for the woman. A healthier lifestyle depends on the earning status of an individual. Without earning, the maintenance of the lifecycle cannot be possible. Pakistan is an underdeveloped country the half proportion of the population consists of women. Women’s participation in the labor force can improve the economy of the country and perform an active role in finishing poverty in Pakistan. The current study has been conducted from Balochistan, the most backward province of Pakistan. The people of Balochistan have strict cultural values and a tribal system, where the best place for women to stay is around the four walls of the home. They are not allowed to work outside the home. The number of working women is less as compared to men in the formal sector. The research aims to highlight the problems of women's employment due to male dominancy at the workplace. The nature of the study is quantitative; the area of study is higher educational institutes of Quetta Balochistan. Through simple random sampling, 500 respondents were selected. Data was collected through a structured questionnaire. The hypothetical statement was tested by the chi-square test. The p-value of the chi-square is lesser than 0.05. The results of the study show that due to the male-dominancy women do not have equal opportunities of selection at the workplace. The males' strong positions in the labor market create hurdles regarding women's employment. This study will be helpful for economists, the social welfare department, women development programs, different NGOs working for women's development to introduce policies for women's employment.